Why Does She Move? : A Study of Women's Mobility in Latin American Cities - Dominguez Gonzalez, Karla; Machado, Ana Luiza; Bianchi Alves, Bianca; Raffo, Veronica; Guerrero, Sofia; Portabales, Irene (World Bank, Washington, DC, 2020)
This study explores the range of constraints to women’s mobility and access to economic opportunities in six low-income areas of urban Latin America through the lens of agency. The study demonstrates that, apart from transport-related deficiencies, several factors at the community, household, and individual levels shape women’s capacity to make and act upon decisions about their mobility. The study consists of five sections in addition to this introduction. Section two: authors discuss key findings from the literature on women’s mobility and how they inform the study design; section three: authors briefly present the methodology; section four: authors describe the factors which shape women’s Agency in Mobility and seek to show how these shape women’s decisions regarding mobility and work; sections five and six: authors draw policy recommendations and conclusions.